Characterisation of circadian rhythms of various duckweeds. (18th June 2014) - Muranaka, T.; Okada, M.; Yomo, J.; Kubota, S.; Oyama, T.
Abstract: The plant circadian clock controls various physiological phenomena that are important for adaptation to natural day–night cycles. Many components of the circadian clock have been identified in Arabidopsis thaliana, the model plant for molecular genetic studies. Recent studies revealed evolutionary conservation of clock components in green plants. Homologues of clock‐related genes have been isolated from Lemna gibba and Lemna aequinoctialis, and it has been demonstrated that these homologues function in the clock system in a manner similar to their functioning in Arabidopsis . While clock components are widely conserved, circadian phenomena display diversity even within the Lemna genus. In order to survey the full extent of diversity in circadian rhythms among duckweed plants, we characterised the circadian rhythms of duckweed by employing a semi‐transient bioluminescent reporter system. Using a particle bombardment method, circadian bioluminescent reporters were introduced into nine strains representing five duckweed species: Spirodela polyrhiza, Landoltia punctata, Lemna gibba, L. aequinoctialis and Wolffia columbiana . We then monitored luciferase (luc+) reporter activities driven by AtCCA1, ZmUBQ1 or CaMV35S promoters under entrainment and free‐running conditions. Under entrainment, AtCCA1::luc+ showed similar diurnal rhythms in all strains. This suggests that the mechanism of biological timing under day–night cycles is conserved throughout the evolution of duckweeds. Under free‐running conditions, we observed circadian rhythms of AtCCA1::luc+, ZmUBQ1::luc+ and CaMV35S::luc+ . These circadian rhythms showed diversity in period length and sustainability, suggesting that circadian clock mechanisms are somewhat diversified among duckweeds.